Nonformal Education Strategy for Social Inclusion: An Analysis of National Policies - Khamidah, Anisa; Fakhruddin, Fakhruddin; Yusuf, Amin (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2025)
This study aims to analyze how national policies conceptualize inclusion through nonformal learning pathways and evaluates their operational effectiveness. It examines the role of nonformal education as a strategic tool for social inclusion in Indonesia, focusing on the persistent gap between symbolic policy commitments and transformative educational practices. Using a qualitative approach with a critical analytical literature review design, data were gathered through systematic analysis of policy texts, academic publications, and institutional reports. Thematic content analysis was used to identify patterns in discourse and policy orientation. Findings indicate that current policies prioritize vocational and administrative objectives while neglecting community-based inclusive learning practices. Structural fragmentation, limited state support, and the absence of an inclusive pedagogical framework weaken implementation. This study underscores the urgency of integrating nonformal education into the national inclusivity framework, supported by measurable indicators and cross-sectoral coordination. The uniqueness of this study lies in bridging critical pedagogy and inclusivity theory to position nonformal education as a transformative and policy-relevant domain in Indonesia.